Hitler [videorecording] - Lagone, Patrick; Martin, Kingsley (Heroes and tyrants of the twentieth century series, 1990)
Presents the fury of Adolf Hitler who ruthlessly dominated Europe for over four years inflecting misery and destruction. Included is footage of Hitler's brown-shirted storm troopers and his meetings with Chamberlain, Mussolini and Stalin, as well as his massacre of the Russian people.